Study of Self-Compatibility Character Related to Seed Characteristics and Seedling Performance on Cocoa - Indah Anita-Sari; Sobir .; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2017)
Self-incompatibility is an important factor in limiting the yield of cacao (Theobroma cacao L.). The research aimed to study the effect of self-compatibility on cocoa related to pod and bean characteristics and seedling performance. The research was conducted at Kaliwining Research Station, Indonesian Coffee and Cocoa Research Institute, Jember and Bogor Agriculture University in Bogor. The research used completely randomized design with three clones as treatment and each treatment repeated three times. The three clones used had a different self-compatibility characteristics; NA 32 (self-incompatible), DR 2 and Sulawesi 2 (self-compatible). Fruit set, pod characteristics, bean characteristics and seedling performance were observed. The results showed that self compatible cocoa clones had higher of fruit set per cushion (4,7-7,9 fruit set per tree) than selfincompatible (1,9 fruit set per cushion). Sulawesi 2 as a self compatible cocoa clone showed the lowest of fallen fruit set per cushion after two and four weeks. Self compatible cocoa clones (Sulawesi 2 and DR 2) had greater pod and better bean quality than self incompatible (NA 32) included pod length, pod weight, pod girth, weight of wet beans per pod, number of beans per pod, volume per wet bean, weight of dry bean and weight of nib. While number of poorly beans per pod in self incompatible showed higher than self compatible clones. Seedling performance of self compatible showed better than self incompatible for plant height and stem diameter. Visually the seedling of self compatible showed homogeny than self incompatible and variant analysis of plant height showed that self compatible were lower than self incompatible.